Pengaruh Perubahan Penggunaan Lahan Hutan Alam Menjadi Hutan Tanaman Industri (HTI) Acacia crassicarpa terhadap Beberapa Sifat Fisika dan Sifat Kimia Tanah Gambut - Amri, Al Ikhsan; Nelvia, Nelvia; Wardati, Wardati; Khotimah, Khusnul; Noviria, Ade (Jurnal Agro Teknologi Tropika, 2015)
The purpose of this research was determine how the effect of lands use change from natural forest to plantationforest Acacia crassicarpa on some physical properties and chemical properties of peat soil. The research conducted inthe PT. BBHA, Bukit Batu Subdistrict, Bengkalis Regency, and Laboratory of Soil Science Agriculture Faculty, RiauUniversity. The research was conducted by survey method, with purposive sampling. Data was analysed by descriptiveand graphics model. The parameters were particle size distribution, bulk density, particle density, porosity, pH, organiccarbon, total nitrogen, total phosphor and base cations (K, Ca, Mg and Na). The result of research show that land usechange from natural forest to plantation forest Acacia crassicarpa was increasing total of smalles particle, bulk density,and particle density, while the porosity decreases. Then the increasing were pH, total nitrogen, total phosphor, and basecations K, Ca, Mg, Na is fluctuative, whereas for organic carbon was linierly. The longer time of land use change wasincreasing the decomposition of peat soil, which improves the physical properties and chemical properties of peat soil.